'He is like a Gazelle (when he runs)' (re)constructing race and nation in match-day commentary at the men's 2018 FIFA World Cup - Campbell, Paul Ian; Bebb, Louis (Sport in society, 2022)
The paper examines the language and racial framing used by match commentators and panellists when describing football players at the 2018 men's Fédération Internationale de Football Association (FIFA) World Cup finals. The paper shines light on the extent to which positive praise continues to differ for different visibly 'raced' players within and across the 19 of the 32 national teams that competed at the 2018 finals. The data are drawn from content analysis of 2700 minute of television coverage taken from 20 purposively selected matches shown on the British Broadcasting Corporation's (BBC) and Independent Television (ITV) television channels in Britain. Results indicate that positive praise differed significantly for differently raced players and it conformed to, and reproduced, wider racial stereotypes and myths. They also indicate that positive praise for men of the same racial category was disrupted by national affiliations and geographic locations, especially for majority white Eastern-European national teams, whose narratives drew heavily instead on 'cold war' discourses and imagining.